Designing School Building Maintenance Priorities Using the Cost-User Effectiveness Ratio - Purwosri, Visaretri Pramuktia; Prasetyo, Hari; Solikin, Mochamad; Harnaeni, Senja Rum; Sunarjono, Sri (ComTech: Computer, Mathematics and Engineering Applications, 2025)
Prioritizing school building maintenance solely based on structural damage often leads to inefficient budget allocation and fewer beneficiaries. The research introduced an integrated Cost-User Effectiveness Ratio (CUER) to establish maintenance priorities by combining three critical factors: damage severity, maintenance costs, and the number of affected students. The CUER formulation employed the Geometric Mean or the root mean multiplication of the cost effectiveness and user effectiveness ratio to balance these factors systematically. The methodology encompassed several steps, including damage assessment and calculation of component importance weights using the Analytical Hierarchy Process (AHP), to determine integrated damage levels, costs, and student weights. These inputs were subsequently used to generate priority rankings of schools requiring maintenance. As a result, the case study in Wonogiri Regency illustrates the superiority of the proposed method over the conventional method. While the conventional approach prioritizes 27 schools benefiting 2,442 students, the CUER approach prioritizes 33 schools benefiting 2,957 students, demonstrating increased efficiency and broader impact. The CUER-based model presents a systematic and equitable solution to prioritize school building maintenance, ensuring the optimal allocation of resources and maximizing benefits within existing budgetary constraints. This innovative approach addresses current challenges in maintenance planning and offers significant implications for improving the management of educational infrastructure.